The impact of light source technology and colour temperature on the well-being, mental state and concentration of shop assistants. (June 2015) - Denk, E; Jimenez, P; Schulz, B
This study examined the impact of light source (LED and HID) and correlated colour temperature (warm-white and neutral-white) on the well-being, mental state and concentration of shop assistants. The experimental design was a 2 × 2 design with repeated measures and complete permutation on all factor combinations with 48 participating shop assistants. Results showed effects of the colour temperature on the well-being and mental state of the shop assistants. No effects of light source could be found for the explored variables. Warm-white colour temperature positively affects the intensity of well-being and mental state and negatively affects the power of concentration.